1987
DOI: 10.1159/000461623
|View full text |Cite
|
Sign up to set email alerts
|

WES, a ‘New’ Infrequent Blood Group Antigen in Finns

Abstract: A previously unrecognized infrequent blood group antigen WES occurs with a frequency of 0.56% in the Finnish population, but has an ethnically restricted distribution. Apart from Finns it was found only in 2 donors, most likely of African origin, among 4,655 people tested who represented many different ethnic groups. WES is shown to be a dominant autosomally inherited character different from previously published infrequent antigens. The data allow exclusion from almost all established blood group systems. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The red cells of Wash, are WES+ and appear to be serologically identical with those of a possible WES+ homozygote described by Sistonen et al [1]. Also, Wash, antibody reacted more strongly in titration with WEScells than with WES+ cells.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The red cells of Wash, are WES+ and appear to be serologically identical with those of a possible WES+ homozygote described by Sistonen et al [1]. Also, Wash, antibody reacted more strongly in titration with WEScells than with WES+ cells.…”
Section: Discussionsupporting
confidence: 77%
“…Sistonen et al [1] showed that WES is present in 0.55-0.60% of Finns but was not found in any other European donors tested. Two of 392 USA donors were WES+: both were probably Black.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations